Long noncoding RNAs CUPID1 and CUPID2 mediate breast cancer risk at 11q13 by modulating the response to DNA damage - Betts, JA; Marjaneh, M; Al-Ejeh, F; Clark, MB (Elsevier, 2017)
Breast cancer risk is strongly associated with an intergenic region on 11q13. We have previously shown that the strongest risk-associated SNPs fall within a distal enhancer that regulates CCND1. Here, we report that, in addition to regulating CCND1, this enhancer regulates two estrogen-regulated long noncoding RNAs, CUPID1 and CUPID2. We provide evidence that the risk-associated SNPs are associated with reduced chromatin looping between the enhancer and the CUPID1 and CUPID2 bidirectional promoter. We further show that CUPID1 and CUPID2 are predominantly expressed in hormone-receptor-positive breast tumors and play a role in modulating pathway choice for the repair of double-strand breaks. These data reveal a mechanism for the involvement of this region in breast cancer.